Advanced lung cancer inflammation index and short-term mortality in sepsis: a retrospective analysis - Li, Junjie; Shao, Yuekai; Zheng, Jie; Dai, Qiuyu; Yu, Kun; Qin, Song; Liu, Xinxin; Mei, Hong (Frontiers in Nutrition, 2025)
BackgroundSepsis is a notable cause of death and poor prognosis in the intensive care unit (ICU). Presents an ambiguous association between advanced lung cancer inflammation (ALI) and short-term lethality in sepsis patients. The purpose of this study is to explore this relationship.MethodsThis retrospective study identified sepsis cases from the MIMIC-IV 3.0 dataset. Multivariable Cox regression analysis was used to evaluate the relationship between ALI and the risks of 30-day all-cause mortality (ACM) and ICU mortality. Kaplan–Meier (K-M) curves and log-rank tests were employed for survival analysis. Restricted cubic spline (RCS) regression was employed to explore the nonlinear association between ALI and mortality risk. Subgroup and sensitivity analyses were performed to confirm the reliability of the results and to evaluate the incremental effect of ALI on the prediction of short-term mortality.ResultsA total of 4,147 sepsis cases were included in this study, with a 30-day ACM rate of 26.7% and a 30-day ICU mortality rate of 18.5%. In the completely adjusted Cox model, patients in the highest quartile of log2-ALI had a 38% lower risk of 30-day ACM (HR = 0.62, p < 0.001) and a 29% lower risk of 30-day ICU mortality (HR = 0.71, p = 0.002) compared to those in the lowest quartile. K-M curves showed that the group with the lowest log2-ALI had the lowest 30-day ACM and ICU survival rates (log-rank p < 0.001). RCS showed a nonlinear relationship between log2-ALI and 30-day ACM (P-overall < 0.001, P-nonlinear < 0.05). In all subgroups, the relationship between log2-ALI and outcomes showed no notable heterogeneity (P for interaction > 0.05), and four different sensitivity analyses yielded robust results. The combination of sequential organ failure assessment (SOFA) score and log2-ALI improved the predictive ability for 30-day ACM, with significant increases in C-statistic, Net Reclassification Improvement (NRI), and Integrated Discrimination Improvement (IDI).ConclusionThis research found that lower levels of ALI were notably linked to higher 30-day ACM and 30-day ICU mortality in sepsis patients, warranting further verification through prospective studies.